FY2016 : FY2018 Medium-Term Budget. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
For the net administrative budget, the FY 16-18 medium-term budget (MTB) proposal includes: In FY 16, an unchanged budget envelope in real terms, for the fourth year in a row. To accommodate new and ongoing strategic priorities of the Fund within a flat envelope, efforts to reallocate resources away from lower-priority activities and achieve efficiency gains were stepped up both at the departmental level and across the institution. Savings measures implying a reallocation of resources of close to 5 percent of the net administrative budget were identified through this process. The bulk of these savings would be used to help meet the new priorities highlighted in the Global Policy Agenda and in Management's Key Goals, while preserving room at the departmental level to further reduce work pressures, phase in the new streamlining measures and, more generally, cope with business uncertainties and unanticipated demands. This robust prioritization effort implies difficult trade-offs and the willingness to cut lower-priority activities in order to create space for new initiatives. For FY 17-18, as a baseline assumption, a flat real budget envelope as well. Against the backdrop of a robust income position, the Fund's medium-term budget formulation is guided primarily by considerations of prudence and credibility. The medium-term spending path will depend on new demands placed on the institution, and the scope for further reprioritization, and will be reassessed in the context of the FY 17-19 budget.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet